Ludificación y neurorrehabilitación motora en niños y adolescentes: revisión sistemática - Pimentel-Ponce, María; Romero-Galisteo, Rita Pilar; Palomo‐Carrión, Rocío; Pinero‐Pinto, Elena; Merchán‐Baeza, José Antonio; Ruiz‐Muñoz, María; Oliver‐Pece, Jesús; González-Sánchez, Manuel (Neurología, 2021)
Introduction: Gamification consists of the use of games in non-playful contexts. It is widely employed in the motor rehabilitation of neurological diseases, but mainly in adult patients. The objective of this review was to describe the use of gamification in the rehabilitation of childrenand adolescents with neuromotor impairment. Methods: We performed a systematic review of clinical trials published to date on the MED-LINE (PubMed), Scielo, SCOPUS, Dialnet, CINAHL, and PEDro databases, following the PRISMA protocol. The methodological quality of the studies identified was assessed using the PEDro scale. Results: From a total of 469 studies, 10 clinical trials met the inclusion criteria. We analysed the gamification systems used as part of the rehabilitation treatment of different neuromotorconditions in children and adolescents. Cerebral palsy was the most frequently studied condition(6 studies), followed by developmental coordination disorder (3), and neurological impairmentof balance and coordination (1). Conclusion: The use of gamification in rehabilitation is helpful in the conventional treatment of neuromotor disorders in children and adolescents, with increased motivation and therapeutic adherence being the benefits with the greatest consensus among authors. While strength, balance, functional status, and coordination also appear to improve, future research should aim to determine an optimal dosage.
Keywords: Sistema nervioso - Enfermedades - Rehabilitación; Videojuegos; Child; Adolescent; Neurological rehabilitation; Video game; Systematic review